2015
DOI: 10.1542/peds.2014-4162
|View full text |Cite
|
Sign up to set email alerts
|

Family Experiences With Feeding Tubes in Neurologic Impairment: A Systematic Review

Abstract: BACKGROUND AND OBJECTIVE: Gastrostomy tubes (G-tubes) are frequently used to provide enteral nutrition for children who have neurologic impairment. Understanding the impact of G-tubes from the family’s perspective will inform decision-making and improve support from health care providers. This study explored the experiences of families after G-tube placement in children with neurologic impairment. METHODS: We conducted a syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
64
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 30 publications
2
64
0
2
Order By: Relevance
“…The literature has shown variability in parent’s experiences for those with a child with a disability after the child’s gastrostomy placement, although enhancement in nutritional status has been reported [3033]. Parents have reported less burden of care at mealtimes, reduced stress that their child is inadequately nourished, and relief that medications are consistently delivered, consequently improving their emotional wellbeing [3034]. In a previous study with primary caregivers of a child with Rett syndrome we found that there was general satisfaction with outcomes following gastrostomy insertion [30].…”
Section: Discussionmentioning
confidence: 99%
“…The literature has shown variability in parent’s experiences for those with a child with a disability after the child’s gastrostomy placement, although enhancement in nutritional status has been reported [3033]. Parents have reported less burden of care at mealtimes, reduced stress that their child is inadequately nourished, and relief that medications are consistently delivered, consequently improving their emotional wellbeing [3034]. In a previous study with primary caregivers of a child with Rett syndrome we found that there was general satisfaction with outcomes following gastrostomy insertion [30].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] This may result in negative feeding experiences for the child and their family, increased risk of choking, vomiting, aspiration pneumonia, 1 growth failure, 5 and higher healthcare cost. These children often have feeding difficulties related to oro-motor dysfunction.…”
mentioning
confidence: 99%
“…These children often have feeding difficulties related to oro-motor dysfunction. [1][2][3] Though gastrostomy and gastrojejunostomy tubes have been shown to improve nutritional outcomes in this population, there is uncertainty regarding their impact on survival, respiratory health, healthcare utilization and cost, feeding times, caregiving burden, and child and primary caregiver quality of life. 6 Gastrostomy and gastrojejunostomy tubes are placed to address these challenges.…”
mentioning
confidence: 99%
“…Taken in a timely manner, the insertion of a GT improves nutritional status and fat mass, decreases respiratory infections and hospitalizations in patients with CP 35,36 . However, patient heterogeneity and measurements, coupled with inadequate design studies make it difficult to demonstrate its benefits [37][38][39] . Moreover, it has been shown that survival at age 19 is greater in those without WG (72% versus 55%) 27 , but this study suggests that the association between WG use and morbidity and mortality should be investigated prospectively , Considering the patient's condition at the time of the WG, in order to evaluate if the greatest risk is real or if it is only about patients with greater fragility and vital risk 5 .…”
Section: Discussionmentioning
confidence: 99%